2010
DOI: 10.1063/1.3326079
|View full text |Cite
|
Sign up to set email alerts
|

Current deep level transient spectroscopy analysis of AlInN/GaN high electron mobility transistors: Mechanism of gate leakage

Abstract: In order to assess possible mechanisms of gate reverse-bias leakage current in AlInN/GaN high electron mobility transistors (HEMTs) grown by metalorganic chemical-vapor deposition on SiC substrates, temperature-dependent current-voltage measurements combined with Fourier transform current deep level transient spectroscopy (FT-CDLTS) are performed in the temperature range of 200–400 K. In this range of temperature reverse-bias leakage current flow is found to be dominated by Poole–Frenkel emission. Based on CDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 18 publications
5
48
0
Order By: Relevance
“…This very low leakage is linked to high-insulating GaN buffer and high quality Schottky diode as well as absence of defects into the upper InAlN barrier layer resulting from high growth quality by PMOCVD, as revealed that the gate reverse-bias leakage current is associated with dislocations in the InAlN barrier layer. 23 As shown in Fig. 4, when the device is pinched off below À7 gate bias, the drain leakage current is dominated by reverse-biased gate current, and no leakage current through the buffer is observed, which is in agreement with the device process result and a proof of highresistive GaN buffer.…”
Section: Resultssupporting
confidence: 90%
“…This very low leakage is linked to high-insulating GaN buffer and high quality Schottky diode as well as absence of defects into the upper InAlN barrier layer resulting from high growth quality by PMOCVD, as revealed that the gate reverse-bias leakage current is associated with dislocations in the InAlN barrier layer. 23 As shown in Fig. 4, when the device is pinched off below À7 gate bias, the drain leakage current is dominated by reverse-biased gate current, and no leakage current through the buffer is observed, which is in agreement with the device process result and a proof of highresistive GaN buffer.…”
Section: Resultssupporting
confidence: 90%
“…So, η and Φ b are equal to 3.7 and 0.53 eV, respectively. The origin of the high ideality factor may be related to a generationrecombination, or Poole-Frenkel or tunnelling mechanisms [8]. No change in η and Φ b has been observed after an ageing time of 216 h. Similarly, the pinch-off voltage (V P ) stayed equal to − 4 V after the ageing test.…”
Section: On-state Stressmentioning
confidence: 96%
“…However, there is generally very high gate leakage current density of Schottky contacts under reverse bias, which is a severe problem hindering the applications of In x Al 1−x N / GaN HEMTs. 1,5,6 Arslan et al, 5 Chikhaoui et al, 6 and Donoval et al 7 analyzed the mechanisms of gate leakage current of Schottky contacts on In x Al 1−x N / GaN heterostructures. They suggested that the reverse-bias gate leakage current was dominated by Frenkel-Poole emission associated with dislocations in the In x Al 1−x N barrier.…”
mentioning
confidence: 99%